Pelaksanaan Tanggung Jawab Sosial Perusahaan PT. Reminal Utama Sakti Terhadap Masyarakat Di Kecamatan Fena Fafan Kabupaten Buru Selatan - Akipatty Alex Solissa; Teng Berlianty; Marselo Valentino Geovani Pariela (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Companies in the laws and regulations can first be found in the second chapter of Article 6 of the Commercial Code (KUHD) it is stated that a person who regulates a company.Purposes of the Research: This writing aims to examine and find out how the form of Corporate Social Responsibility of PT. Reminal Utama Sakti on improving the welfare of the people of Fena Fafan Subdistrict, South Buru Regency, to study and determine the effect of implementing Corporate Social Responsibility PT. Main Reminal Sakti towards Improving Community Welfare, Fena Fafan Sub-district, South Buru Regency.Methods of the Research: Normative juridical research method, which is to obtain data from the library in the form of documents, books, magazines and other literature related to writing. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as a technique for collecting legal materials, then processing and analyzing legal materials through qualitative analysis, namely the data obtained and then arranged systematically for further qualitative analysis based on scientific disciplines. civil law to achieve clarity of issues to be discussed.Results of the Research: The results showed that PT.Reminal Utama Sakti Forms CSR Corporate Social Responsibility to the Community of Fena Fafan District, South Buru Regency. Diesel Fuel Assistance for the Waekatin GPM Church, Diesel Fuel Assistance for Waeken Village, Solar Fuel Assistance for Fakal GPM Church, Solar Fuel Assistance for Uneth Village, Solar Fuel Assistance for Siwatlahin Village, Solar Fuel Assistance for the Mengeswaen GPM Church, Solar Fuel Assistance for the Church Waelo GPM, Diesel Fuel Assistance for Waeraman Village, Solar Fuel Assistance for Batukarang Village, Solar Fuel Assistance for Nusarua Village, and Community Empowerment Fund Assistance Fund allocation of Rp. 400.000 CSR Management Techniques at PT.Reminal Utama Sakti Through Proposals or Request Letters From the Community or Stakeholders in Fena Fafan Sub-district Then a request or request from the community or existing stakeholders is realized by the company. Corporate Social Responsibility in accordance with article 74 paragraph (1) and paragraph (2) of Law no. 40 of 2007 Forms of Social Responsibility in PT.Reminal Utama Sakti Company have not been properly realized to the Community Environmental Responsibility, in accordance with article 28H of the 1945 Constitution of the Republic of Indonesia and article 1 paragraph (2) of Law no. 32 of 2009 In order to return to the environmental conditions before forest exploitation. Region (Perda) No. 9,ld.2014/5.Tld no 37,ll Regional Secretariat of Maluku Province.